1992
DOI: 10.1007/bf00922094
|View full text |Cite
|
Sign up to set email alerts
|

Optical magnification as event information

Abstract: The geometrical optics of approach events is delineated. It is shown that optical magnification provides information about distance and time until collision. An experiment is described in which two objects--white styropor spheres 10 cm in diameter, seen against a white plaster wall--were moved simultaneously at equal, constant speed along straight, converging paths at eye level towards a human observer and towards a common, virtual point of collision which either coincided with the observer's station point or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Results of Experiment 4 showed substantial underestimation for trajectories 45° from transverse, and unpublished data (Schiff, 1988) have also shown intermediate amounts of judgment error for trajectories only 10° elevated from the scalar eye height of the top of approaching autos. Kebeck and Landwehr (1988) found phenomena very similar to those reported here by using objects (model trains) approaching observers or each other at eccentric angles in real 3-D space, implying that our findings are not restricted to filmed space. Head-on T a estimates are for the most part underestimates, that is, conservative constant errors.…”
Section: Discussionsupporting
confidence: 89%
“…Results of Experiment 4 showed substantial underestimation for trajectories 45° from transverse, and unpublished data (Schiff, 1988) have also shown intermediate amounts of judgment error for trajectories only 10° elevated from the scalar eye height of the top of approaching autos. Kebeck and Landwehr (1988) found phenomena very similar to those reported here by using objects (model trains) approaching observers or each other at eccentric angles in real 3-D space, implying that our findings are not restricted to filmed space. Head-on T a estimates are for the most part underestimates, that is, conservative constant errors.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the demonstrated insufficiency of tau, TTA judgments are known to be mediated by several variables that are not related to tau, such as the absolute amount of optical magnification (Kebeck & Landwehr, 1993), changing target vergence (Heuer, 1993), and perceived velocity (Smeets, Brenner, Trébuchet, & Mestre, 1996). Furthermore, DeLucia (1991; DeLucia & Warren, 1994) showed that relative size as a static depth cue supersedes motion-based depth information for objects on a collision trajectory.…”
Section: Doubts About Global Taumentioning
confidence: 99%
“…For head-1 As has also been noted by others (e.g., Bootsma & Craig, 2002, p. 918, note 6), in Todd's (1981) experiment, approach was not head-on in the sense of the two objects' midpoints traveling on converging trajectories toward the observer (cf. Kebeck & Landwehr, 1992, for such a scenario); rather, the two objects were set side by side, so that the two abutting lateral edges traveled on a collision course along the observer's cyclopean line of gaze. centered, straight trajectories, the optic flow field's focus of expansion coincides with the object's or the observer's direction of travel and gaze (Warren, 1998), and global τ, at this point, is undefined (or zero).…”
Section: Stimulimentioning
confidence: 99%